The influence of internal marketing on job satisfaction in the Romanian public sector and the mediating role of empowerment - Bunea, Ovidiu-Iulian; Popescu, Ruxandra-Irina; Corboș, Răzvan-Andrei; Sabie, Oana-Matilda; Trușcă, Marian Iulian (Journal of Business Economics and Management, 2025)
The public sector has made significant innovations in its contemporary operations. Beyond digitisation, enhancing the processes involving public servants is necessary to provide effective service to citizens. This study examines the connection between internal marketing strategies and job satisfaction among public sector employees in Romania. Through quantitative analysis and a questionnaire-based approach, the research explores various internal marketing dimensions such as communication, training, rewards, and empowerment. Using robust statistical methods, particularly partial least squares structural equation modelling (PLS-SEM), the study explores the complex relationships between these dimensions and job satisfaction. Aligned with the principles of new public management (NPM), this research pioneers the investigation of internal marketing in the public sector. The findings reveal nuanced dynamics, demonstrating that while internal communication indirectly influences job satisfaction by empowering employees, training has a direct impact. Additionally, fair reward systems directly contribute to satisfaction, while empowerment emerges as a significant standalone factor. The study emphasises the importance of strategic programme design in communication, training and rewards, recognizing empowerment as a key driver of job satisfaction among public sector employees.